DESKRIPSI MATERI PEMBELAJARAN BAHASA PRANCIS PADA BUKU TEKS AGENDA 1 - Junianti, Nia (2015)
The textbook is one of the media that is still used now. In the French language learning, there are a variety of textbooks published to support the learning process, one of them is Agenda 1. Before using a textbook, we have to analysis the contents of the book. Therefore, the description of textbooks Agenda 1 was conducted to determine general information or the profile of the book, describing the structure of the material, and to exposing the core of the French language materials in accurate with the language skills listening, reading, speaking, and writing based on le Cadre EuropéenCommun de Référence pour les Langues (CECRL) levels A1. The method in this research is descriptive method with a sample is the overall French language material in the textbook Agenda 1. The results of this reseach showed that the material in the textbook Agenda 1 is well presented and the criteria CECRL levels A1 has been available in this textbook. Therefore, the textbookAgenda 1 can be a source for learning French language at elementary level. Keywords: textbooks, material learning, Agenda 1 ABSTRAK Bukuteksmerupakansalahsatumediapembelajaran yang masihdigunakanhinggasaatini.DalampembelajaranbahasaPrancis, terdapatberbagaibukuteks yang diterbitkangunamenunjang proses pembelajaran, salahsatunyaadalahAgenda 1. Namun, pengajartidakbegitusajamenggunakansuatubukuteks, perludilakukantelaahisibukuterlebihdahulu.Olehkarenaitu, penelitianinidilakukanuntukmendeskripsikanbukuteksAgenda 1dengantujuanuntukmengetahuiinformasiumumatauprofildaribukuteks tersebut, mendeskripsikanstrukturmateri di dalamnya, sertamemaparkankedalamanmateribahasaPrancissesuaidenganketerampilanberbahasayaknimenyimak, membaca, berbicara, danmenulissesuaidenganle Cadre EuropéenCommun de Référence pour les Langues (CECRL)tingkat A1. Metode yang digunakandalampenelitianiniyaitumetodedeskriptifdengansampel yang diambiladalahkeseluruhanmateribahasaPrancisdalambuku teksAgenda 1.Hasilpenelitian inimenunjukkanbahwamateridisajikandenganbaikdankriteria CECRL tingkat A1 telahterpenuhidalambukuteks tersebut.Sehingga, Agenda 1dapatmenjadibahan ajar bagimahasiswabahasaPrancistingkatdasar. Kata kunci: buku teks, materipembelajaran, Agenda 1.